How does soil organic carbon mediate trade-offs between ecosystem services and agricultural production? - Villarino, Sebastián Horacio (2019)
The basis and essence of life on earth depends on soil health, and its main indicator is the soil organic carbon (SOC) content. Hence, SOC stock is a key component for the supply of many ecosystem services (SOC-mediated ES), such as erosion protection, nutrient cycling, water regulation, and climate regulation. Land use changes from natural ecosystems into agricultural systems generally deplete SOC stocks. Therefore, agricultural production usually involves trade-off relations with SOC-mediated ES supply. This paper assessed the trade-offs between agricultural production and SOC-mediated ES supply in six sub-regions of Argentina: East Southern Pampa, West Southern Pampa, Flooding Pampa, Central Pampa, Rolling Pampa and Semiarid Chaco. In the Semiarid Chaco, overall SOC-mediated ES supply had the highest sensitivity to SOC changes, and the lowest sensitivity to natural cover removal. In East Southern Pampa, overall SOC-mediated ES supply had the lowest sensitivity to SOC changes and the highest to natural cover removal. The differences in sensitivity of overall SOC-mediated ES supply to the changes in SOC could be explained by soil texture, which is finer at East Southern Pampa. The differences in sensitivity of overall SOC-mediated ES supply to natural cover removal could be associated with the initial SOC stocks, which is lower in the Semiarid Chaco. The high sensitivity of SOCmediated ES to SOC change and the low levels of SOC-mediated ES supply found in the Semiarid Chaco subregion suggests that it is a highly fragile environment. The agricultural expansion over natural areas led to trade-offs between production and SOC-mediated ES supply. However, increasing crop yields would lead to win-win situations, by positive effects on agricultural production and SOC-mediated ES supply. Hence, agricultural production should be increased by increasing crop yields rather than expanding cropland and/or pasture over natural areas.